Cellulite in menopause - Leszko, Marta (Menopause Review/Przegląd Menopauzalny, 2014)
Menopause is a physiological process related to the increasing insufficiency of the hypothalamic-hypophyseal-ovarian axis. The pool of ovarian follicles capable of synthesizing female sex hormones becomes gradually depleted. In response to the sequence of endocrine changes of premenopause, perimenopause, and postmenopause, systemic somatic and emotional disturbances appear. Skin is the target organ for sex hormones. In women, the trophicity and appearance of the skin are most significantly affected by female sex hormones, estrogens and progesterone. However, this review also emphasizes the influences of other hormones on the skin and subcutaneous tissue. During menopause, a low estrogen concentration is responsible for increased vascular permeability and decreased vascular tone, which lead to microcirculation impairment and are important factors predisposing to the development of cellulite. The effects of estrogen deficiency on the skin connective tissue include a decreased production and topical content of both type I and III collagen and elastin fibers, which also contributes to cellulite. This paper presents diagnostic methods and clinical types of cellulite, as well as principal instrumental and manual treatments used for the reduction of the condition. Preparations containing ingredients which help to improve the metabolism of subcutaneous fat and enhance blood and lymphatic circulation, applied in cosmetology and esthetic medicine practice, have been reviewed. Furthermore, we provide an array of opinions regarding the effectiveness of treatment modalities presented here.